Clinical applications of electrical stimulation for peripheral nerve injury: a systematic review - Costello, Meredith C.; Errante, Emily L.; Smartz, Taylor; Ray, Wilson Z.; Levi, Allan D.; Burks, Stephen Shelby (Frontiers in Neuroscience, 2023)
Introduction Peripheral nerve injuries are common neurologic injuries that are challenging to treat with current therapies. Electrical stimulation has been shown to accelerate reinnervation and enhance functional recovery. This study aims to review the literature on clinical application of electrical stimulation for peripheral nerve injury. Methods PubMed and Embase were sourced from 1995 to August 2022. Selection was based on predetermined inclusion/exclusion criteria. Eight hundred and thirty-five articles were screened with seven being included in this review. Results Two hundred and twenty-nine patients with peripheral nerve injuries were represented. Six of the studies were randomized controlled trials. A variety of nerve injuries were represented with all being in the upper extremity and supraclavicular region. Electrical stimulation protocols and evaluation varied. Electrodes were implanted in four studies with one also implanting the stimulator. Length of stimulation per session was either 20 mins or 1 h. Median stimulation frequency was 20 Hz. Stimulation intensity varied from 3 to 30V; pulse width ranged from 0.1 to 1.007 ms. Three protocols were conducted immediately after surgery. Patients were followed for an average of 13.5 months and were evaluated using electrophysiology and combinations of motor, sensory, and functional criteria. Discussion Patients who received electrical stimulation consistently demonstrated better recovery compared to their respective controls. Electrical stimulation for peripheral nerve injury is a novel treatment that has not been well-studied in humans. Our review illustrates the potential benefit in implementing this approach into everyday practice. Future research should aim to optimize protocol for clinical use.